89.7k views
5 votes
When factored completely,x³-13x²-30x is

User Jiayi
by
6.2k points

1 Answer

3 votes

Answer:


x(x+2)(x-15)

Explanation:

we have


x^(3)-13x^(2)-30x

step 1

Factor x


x^(3)-13x^(2)-30x=x(x^(2)-13x-30)

step 2

Find the solutions of
(x^(2)-13x-30)

Complete the square


(x^(2)-13x)=30


(x^(2)-13x+6.5^(2))=30+6.5^(2)


(x^(2)-13x+42.25)=72.25


(x-6.5)^(2)=72.25

square root both sides


(x-6.5)=(+/-)8.5


x=6.5(+/-)8.5


x1=6.5(+)8.5=15


x2=6.5(-)8.5=-2

so


(x^(2)-13x-30)=(x+2)(x-15)

substitute


x^(3)-13x^(2)-30x=x(x+2)(x-15)

User Fuzzzzel
by
5.3k points